Analisis Penyimpanan Arsip Inaktif pada Unit Kerja Human Capital Database di PT X - Stephanie Marsha Sabila; Christian Wiradendi Wolor; Adnan Kasofi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Abstract. Records containing critical information for a company must be managed properly to preserve their utility and role as an authoritative source of information in supporting accountable and transparent administrative. This study aims to provide insights into the causes, solutions, and prevention of issues related to inactive record storage. The storage condition of inactive records in the Human Capital Database at PT X has not been properly implemented. In this research, the author employed a descriptive qualitative research approach. Data collection techniques used included observation, interviews, and documentation. The results of the study indicate that the inactive record storage in the Human Capital Database unit faces challenges due to the increasing volume of records and limited storage space. To address these issues, the proposed solution involves transferring inactive records to archival partners to be converted into static records. This effort is undertaken to prevent the accumulation of inactive records in storage.